Promoting entomophagy as a response to food insecurity through the development of suitable food products - Murdock, Robert S (2023)
Utilisation of insects as food is a rapidly expanding global market due to insect’s viability as a sustainable and economical source of high-quality protein. While they are traditionally consumed in many countries, in the Western world it is still unclear how best to exploit this new resource, while conforming to speculative safety regulations. Although literature demonstrates the highly malleable and varied nature of insects as a food source, a powder, produced from crickets, is seen by many as a versatile and nutritious form in which insect-derived food may be accepted in Western culture. The primary aim of this study was to take four cricket species (Gryllus bimaculatus, Gryllodes sigillatus, Gryllus assimilis, Acheta domesticus) and Desert locust (Schistocerca gregaria) from farm to the fork through exploring the impact of different methods of powder production on the nutritional value and safety of the powder before considering barriers to consumer acceptance and how products containing cricket powder may be produced that are acceptable to such consumers. Some differences were seen in nutritional composition between cricket species, and drying methods impacted on the fatty acid and protein composition. Drying methods also had some impact on the microbial content of the powders. However, in general, all insect species and methods of production yielded a potential food ingredient rich in high quality protein and a range of minerals which, when stored appropriately, represented a low biological risk to the consumer. Further analysis of commercial cricket powder demonstrated the presence of hard to remove pathogenic microorganisms (Bacillus cereus & Bacillus lichenformis), an insecticidal microorganism (Brevibacillus Laterosporus), that may pose an issue for insect farmers, and two organisms with limited previous study (Rummeliibacillus stabekisii & Lysinibacillus Pakistanesis). A survey on consumer perspectives demonstrated clear expectations for insect-based food, as well as biases towards what types of products may be suitable for the UK market and key areas that would be unacceptable to consumers at this stage. Combining all of the information gathered throughout the study, allowed for the development of an alkaline noodle product which provided insight into how the utilisation of insects in food development resulted in a decrease of product quality that could be overcome through adjustments to the formulation. Overall, this project demonstrates that products containing insects can be produced which are safe, and nutritious and potentially suitable for both the promotion of entomophagy in the Western world and combatting a key area of protein malnutrition in South-East Asia.